Developing strength and power - Stone, M. H.; Cormie, P.; Lamont, H.; Stone, M. (Strength and conditioning for sports performance, 2016)
This discussion will also deal briefly with a more traditional approach to periodisation and for programming resistance training to enhance strength and power. For a more detailed discussion of advanced periodised training methods, refer to Chapter 17, as well as Bompa and Haff |24), DeWeese et al. (47, 48], Plisk and Stone [145] and Stone et al. [177]. The outcome of strength and power training and subsequent adaptations are influenced by a variety of factors. Level of athlete, fatigue state, sex, contraction type (e.g. eccentric versus concentric), exercise and training loading schemes are among some of the factors that affect adaptation to training. Although many of the details and mechanisms underlying these factors are only now beginning to emerge, strong evidence exists indicating that the mode and method in which training is presented to the athlete can make a profound difference in the performance outcome [24, 169],